TEORI BELAJAR BAHASA KONTRUKSI KREATIF PADA ANAK SEKOLAH DASAR - Nuriana Azka; Muhamad Rosyid Sobikhi (Jurnal Ilmiah AZZIQRI: Kajian Keislaman dan Kependidikan, 2023)
Education has a very significant goal, namely to hone the abilities or potential of every individual human being so as to form people who have faith, are capable, skilled, have good ethics, are active, are responsible and so on. The learning process can be well established, not without the role of good language use. Language is an ability that is naturally owned or trained over time. Children's views regarding language tend to be imitation or it can also be said that what is heard and seen is then constructed in their thinking so that children will acquire language more quickly. Language acquisition in children cannot be separated from language learning theories such as LAD, monitor, and creative construction. All of these language learning theories are very influential in the development of language acquisition processing in children which are explained by experts. Experts explain according to the views held and research carried out by each party. The research method used is qualitative research.